Multiskilled in Many Ways: Ghanaian Female Journalists between Job and Home - Boateng, Kodwo Jonas Anson; Lauk, Epp (Communication Today, 2020)
In Ghana, the feminisation of the journalism profession has become a fact: more girls are entering journalism programmes in the Universities, and the number of women employees are growing in the newsrooms. The problem of balancing work-time arrangements (e.g. irregular and unpredictable work schedules, weekend work and long working hours) with equally important domestic obligations are familiar to most female journalists around the globe. Even in countries with well-developed social support structures, and well-defined labour laws, the current nature of journalism work-time arrangements impedes many female journalists in achieving worklife balance. For most Ghanaian female journalists, the culturally entrenched disproportionate societal power hierarchies amplify the challenges of the gendered journalism environment. This study employs unstructured in-depth interviews with 23 female journalists from various regions in Ghana. The study explores three sets of arrangements and demonstrates their impact on the ability of female journalists to balance their domestic and work obligations. The study revealed that the not-so-successful efforts of combining their multiple domestic and social obligations with professional ones cause emotional stress, guilt and self-condemnation and further revealed, female regional correspondents tend to have higher levels of work-life imbalance.